Pengembangan Media Pembelajaran Interaktif Pada Materi Momentum dan Impuls Kelas X SMA - Irawan, Haeirani; Taufik, Muhammad; Ayub, Syahrial (Mataram University, 2021)
This research aims to develop interactive learning media on momentum materials and impulses of grade X senior high school and to know the feasibility of interactive learning media. The type of research used is research and development developed by Thiagarajan is 4D (Define, Design, Develop, Disseminate). The results of the products from computer-based interactive learning media with a feasibility category based on media experts of 85% (excellent) and based on material experts of 81% (excellent). Limited trials are not conducted due to limitations of civility and time. It is concluded that this research produces products in the form of learning media software that has an excellent feasibility category